Propriedades espectrais uniformes para operadores de Schrödinger com potenciais Sturmianos - Pigossi, Mariane [UNESP] (2014)
The present work intends to study uniform spectral properties of discrete one-dimensional Schrodinger operators with Sturmian potentials. Based on studies in the literature, it is shown that these operators have purely singular continuous spectrum supported on a set with Lebesgue measure zero. It is also shown that, for Hausdorff measure, such operators with Sturmian potentials generated by rotation number of bounded density have purely -continuous spectrum with 2 (0; 1).